Metadherin–PRMT5 complex enhances the metastasis of hepatocellular carcinoma through the WNT–β-catenin signaling pathway - Zhu, Kai (Carcinogenesis, 2020)
Accumulating data suggest that metadherin (MTDH) may function as an oncogene. Our previous study showed that MTDH promotes hepatocellular carcinoma (HCC) metastasis via the epithelial-mesenchymal transition. In this study, we aim to further elucidate how MTDH promotes HCC metastasis. Using Co-immunoprecipitation (co-IP) and mass spectrometry, we found that MTDH can specifically bind to protein arginine methyltransferase 5 (PRMT5). Further functional assays revealed that PRMT5 overexpression promoted the proliferation and motility of HCC cells and that knockout of PRMT5 impeded the effect of MTDH. The immunohistochemistry assay/tissue microarray results showed that when MTDH was overexpressed in HCC cells, PRMT5 translocated from the nucleus to the cytoplasm, with the subsequent translocation of β-catenin from the cytoplasm to the nucleus and upregulation of the WNT–β-catenin signaling pathway. Further in vivo experiments suggested that PRMT5 and β-catenin played a pivotal role in MTDH-mediated HCC metastasis. We therefore concluded that the MTDH–PRMT5 complex promotes HCC metastasis by regulating the WNT–β-catenin signaling pathway.